Atmosphere, climate, and change - Graedel, T. E.; Crutzen, Paul J., 1933- (New York : Distributed by W.H. Freeman, 1995)
Discusses the atmosphere as a system and relationship to the planet Earth. Explores climate change, scientific predictions, and what we can do about them.
Taking the pulse of Earth -- Agents of climate -- Chemistry in the air -- Climates of the past -- Changing chemistry -- Predicting the near future -- Predicting the far future -- Of change and sustainability.
Includes bibliographical references and index.
Kliatt.
Adult.
Young Adult
Keywords: Atmospheric chemistry; Climatology; Atmosphere; Climate